AN ANALYSIS OF THE CHILDREN’S CHARACTERS IN ROALD DAHL’S NOVEL: CHARLIE AND THE CHOCOLATE FACTORY - Hissan, Wan Syakira Meor (Indonesian Journal of Applied Linguistics, 2012)
Abstract: Children's literature or children's books particularly by Roald Dahl have been adapted into many films and have received overwhelming response from children all over the world. Unlike novels for the adults, children's books explore the conflicts and challenge the children's characters encounter in their everyday lives. In addition, the issue of morality and moral values are always associated with the children's books. Thus, this research aims to discuss morality by analysing the children's characters in Charlie and the chocolate factory (1964) by Roald Dahl. The main focus of this study is the children’s mature and immature morality that is potentially helpful to assist teachers and parents to be aware of the moral values highlighted in children’s books. Gibbs’ Revisionist Model is used in order to analyse the mature and immature morality of the children’s characters. This study adopts a textual analysis in order to reveal the children’s characters’ morality and the moral values arising from the texts. The findings intend to demonstrate that children's books, particularly this novel, is relevant to be used as a medium to promote moral values.Keywords: moral development, morality, moral knowledge and moral values